MUMMIFIED PAPYRACEOUS FETUSES IN THE ABDOMINAL CAVITY OF A DASCHUND BITCH - A CASE REPORT - ANUSHA, K; RAJ, M PRAVEEN; NAIDU, G VENKATA (The Indian Journal of Animal Reproduction, 2023)
This paper reports on successful surgical treatment of papyraceous mummified fetuses in the abdominalcavity of a 6 year old Daschund bitch.
Keywords: Papyraceous mummification; Uterine rupture; Bitch